[RETRACTED] PENGARUH EXPERIENTIAL VALUE DAN PLACE FOOD IMAGE YOGYAKARTA TERHADAP BEHAVIORAL INTENTIONS WISATAWAN DOMESTIK - Nita Lintang Sekarrini; Siti Rahayu; Erna Andajani (CALYPTRA, 2019)
[THIS ARTICLE HAS BEEN RETRACTED] Following a rigorous, carefully concerns and considered review of the article published in CALYPTRA to article entitled "PENGARUH EXPERIENTIAL VALUE DAN PLACE FOOD IMAGE YOGYAKARTA TERHADAP BEHAVIORAL INTENTIONS WISATAWAN DOMESTIK" Vol.7 No 2, pp.2465-2473, March 2019 The document and its content has been removed from CALYPTRA, and reasonable effort should be made to remove all references to this article.